Evaluasi Kinerja Unit Produksi Asam Sulfat (WSA) pada Proses Produksi Gas Alam - Bundang, Syarifullah; Amir, Muh. Karnoha (CV Insight Publisher, 2024)
Feed gas which is produced by the factory of gas processing generally contains acid gas with high concentrations of acid gas wich must be removed by reducing the contrentration of CO2 and H2S according to product specification of sweet gas of <4 ppm-mol H2S and 5 % CO2. The research on the unit of WSA aimed to compare the simulated data and actual performance data and trial simulation (combustion pressure, the inlet temperature of SO2 converter, and water excess. The method used to retrieve the actual data of each piece of equipment was the results of the analysis of the composition of the acid gas, the composition of the stack, and purity H2SO4. The results obtained showed that the conditions of the performance test and simulation are not significantly difference, yet the purity H2SO4 obtained from the simulation results higher than the performance test. Based on the results of observations showed that the higher the molar flow acid gas is the higher the flow rate of the inlet will be and influence to the products where the flow rate of H2SO4 will decline, when water excess is added, the purity of the product will increase, and the flow rate of product will decline. There are differences in the purity of H2SO4 from the performance test and simulation.